Salivary Duct Carcinoma: An Aggressive Salivary Gland Malignancy with Opportunities for Targeted Therapy - Schmitt, Nicole C. (Oral Oncol, 2017)
Salivary duct carcinoma (SDC) is a rare, aggressive salivary malignancy that is often diagnosed at an advanced stage. Previously, little was known about outcomes of this disease due to its rarity. In the past several years, much has been learned about salivary duct carcinoma after publication of outcomes from several large single-institution series and national database searches. Recent studies of genomic alterations have helped elucidate the biology and pathogenesis of this aggressive disease. Here we review outcomes of the disease, effects of treatment, prognostic factors, and genomic alterations in SDC. Studies of targeted therapy and promising future directions are also discussed.